(m,a,n)-Fuzzy Neutrosophic Sets and Their Topological Structure - Samajh Singh Thakur; Saeid Jafari (Neutrosophic Sets and Systems)
In this paper the concept of (m, a, n)-fuzzy neutrosophic set is introduced and its basic operations are studied. It is shown by examples that the class of (m, a, n)-fuzzy neutrosophic sets properly contains the class of q-rung orthopair neutrosophic sets. Moreover, a topological structure on (m, a, n)-fuzzy neutrosophic sets is created, and the topological notions such as closure, interior, subspace, connectedness, and separation axioms, are extended to (m, a, n)-fuzzy neutrosophic sets and explore their properties in (m, a, n)-fuzzy neutrosophic topological spaces.